CLARITY‐BPA academic laboratory studies identify consistent low‐dose Bisphenol A effects on multiple organ systems. (17th October 2018) - Prins, Gail S.; Patisaul, Heather B.; Belcher, Scott M.; Vandenberg, Laura N.
Abstract: Bisphenol A (BPA) is a high‐production chemical used in a variety of applications worldwide. While BPA has been documented as an endocrine‐disrupting chemical (EDC) having adverse health‐related outcomes in multiple studies, risk assessment for BPA has lagged due to reliance on guideline toxicology studies over academic ones with end‐points considered more sensitive and appropriate. To address current controversies on BPA safety, the United States National Institute of Environmental Health Sciences (NIEHS), the National Toxicology Program (NTP) and the Food and Drug Administration (FDA) established the Consortium Linking Academic and Regulatory Insights on BPA Toxicity (CLARITY‐BPA) using the NCTR Sprague‐Dawley rats. The goal of CLARITY‐BPA is to perform a traditional regulatory toxicology study (Core study) in conjunction with multiple behavioural, molecular and cellular studies by academic laboratories focused on previously identified BPA‐sensitive organ systems (Academic studies). Combined analysis of the data from both study types will be undertaken by the NTP with the aim of resolving uncertainties on BPA toxicity. To date, the Core study has been completed and a draft report released. Most of the academic studies have also been finalized and published in peer‐reviewed journals. In light of this important milestone, the PPTOX‐VI meeting held in the Faroe Islands, 27‐30 May 2018 devoted a plenary session to CLARITY‐BPA with presentations by multiple investigators with the purpose of highlighting key outcome. This MiniReview synthesizes the results of three academic studies presented at this plenary session, evaluates recently published findings by other CLARITY‐BPA academic studies to provide an early combined overview of this emerging data and places this in the context of the Core study findings. This co‐ordinated effort revealed a plethora of significant BPA effects across multiple organ systems and BPA doses with non‐monotonic responses across the dose range utilized. Remarkably consistent across most studies, including the Core study, are low‐dose effects (2.5, 25 and 250 μg BPA/kg body‐weight). Collectively, the findings highlighted herein corroborate a significant body of evidence that documents adverse effects of BPA at doses relevant to human exposures and emphasizes the need for updated risk assessment analysis.